Bauran Promosi Jasa Hotel - Cut Faradilla Dinda Wibowo; Anne Ratnasari (UNISBA Press, 2023)
Abstract. Developments in the business world are increasingly advanced and broad, such as companies engaged in hospitality services. Grand Praba Bandar Hotel Lampung is one of the three-star hotels that embeds and has elements of the culture and history of Lampung Province. Grand Praba Hotel Bandar Lampung provides various kinds of quality services so that hotel guests can be satisfied with the services that have been provided. This study aims to determine the form of the promotion mix, the use of promotional media, obstacles in the hotel service promotion mix and efforts to overcome them, and to find out the reasons for applying the concept of